The Impact of Affixes on EFL Students' Sentence Comprehension - Jouda, Adil (Al-Adab Journal, 2025)
From the first sight, the relation between the morphological units, i.e., affixes, and sentence comprehension seems to be remote, yet deep scrutiny reveals that the relation is quite close as these units, in addition to other factors, have a crucial role in determining word meanings and consequently sentence meanings.This paper is intended to investigate this role and highlight the impact of the affixes on EFL students' sentence comprehension.A test has been conducted to (29) BA students randomly chosen for the test using Google forms. Each student is required to answer (15) items. Each item contains a word having an affix. Based on students' answers, where one third of their responses was erroneous, the study concludes that suffixes have a negative impact on students' sentence comprehension, which indicates students' unawareness of the importance and contribution of these suffixes in the construction of sentence meaning.As far as prefixes and their role in students' sentence comprehension are concerned, it has been clear that they have less impact on sentence comprehension as their meanings are relatively predicable standing for prepositions or negation, unlike the suffixes that have numerous flexible meaning facets.